2021
DOI: 10.3390/su13020793
|View full text |Cite
|
Sign up to set email alerts
|

Towards Sustainable Residential Buildings in Saudi Arabia According to the Conceptual Framework of “Mostadam” Rating System and Vision 2030

Abstract: Saudi Arabia vision 2030 adopts comprehensive development standards in all fields of Saudi society. To achieve such standards, many initiatives and programs have been launched to achieve sustainable goals while meeting the needs of the present without compromising the requirements of future generations. Sustainable buildings are highly important in achieving sustainable development goals due to their excellent ability to reduce energy consumption, increase building efficiency, and reduce harmful emissions of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 26 publications
1
37
0
Order By: Relevance
“…On the other hand, weather conditions, building characteristics, equipment owner level, and occupant behavior are the main parameters affecting this energy consumption. Balabel and Alwetaishi [16] examined different topics connected to developing the sustainable buildings sector, focusing on residential buildings in KSA. Moreover, the authors compared between suggested national rating system for buildings rating with the international LEED system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, weather conditions, building characteristics, equipment owner level, and occupant behavior are the main parameters affecting this energy consumption. Balabel and Alwetaishi [16] examined different topics connected to developing the sustainable buildings sector, focusing on residential buildings in KSA. Moreover, the authors compared between suggested national rating system for buildings rating with the international LEED system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results from this survey question can reinforce the larger points in the water category under Mostadam when comparing it to LEED. Further analysis in this specific category has been published by Balabel and Alwetaishi [69]. When comparing the level of points awarded in the water category, Mostadam awards higher points than LEED.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, building designs should be optimised for the local climatein KSA there are several distinct climatic zones across the country that should be considered 251 . UAE has introduced locally-relevant building codes, but existing building codes still need further review to explore how new sustainable building codes and policy intervention might be used to drive the most appropriate developmentfor example, some of the LEED building standards are inappropriate for hot climates 256 . Both KSA and UAE are investing in green buildings applying the latest LEED building codes, and undertaking some retrofit initiatives 256,257 .…”
Section: Built Environment and Habitability (3ci Overview)mentioning
confidence: 99%
“…UAE has introduced locally-relevant building codes, but existing building codes still need further review to explore how new sustainable building codes and policy intervention might be used to drive the most appropriate developmentfor example, some of the LEED building standards are inappropriate for hot climates 256 . Both KSA and UAE are investing in green buildings applying the latest LEED building codes, and undertaking some retrofit initiatives 256,257 . For example, Abu Dhabi has rolled out an initiative to retrofit government buildings, and Dubai has set a target to retrofit 30,000 buildings by 2030 2 .…”
Section: Built Environment and Habitability (3ci Overview)mentioning
confidence: 99%
See 1 more Smart Citation